A novel painted monument. Byzantine Art between Aesthetic Redefining and Dogmatic Perennity. The church Saint John the Baptist of Bârnova - Mihail M. Gheaţău (Anastasis: Research in Medieval Culture and Art, 2015)
Being remarkable through the monumentality and elegance of proportions, the architecture of the Church “Saint John the Baptist” from Bârnova derives from the so-called old Wallachian style, skillfully reshaping a structure which combines elements which are specific to Byzantine Balkanic ecclesiastical buildings. The unseen pictural work of Ștefan Constantinescu is characterized by the attempt to associate the results of experiencing freedom of interpretation and expression with the rules of the iconographic canon, inside the same ensemble. Its representations do not reproduce the traditional Byzantine manner, nor it is delivered as a form of quoting reality, but it is filtered and interpreted. From a theological point of view, the author respects the iconographic program, except for the topographic placement of some episodes, adapting the discourse according to the configuration and features of the liturgical space. We are in front of a case which places us in the position of managing the relationship between the value of artistic creation and the meticulosity of theological involvement. Neither Byzantine, nor realistic, the artistic solution of the mural painting from Bârnova is closer to the manner of iconic transfiguration than to the one of improvisation or artistic intermediation through which the daily tridimensional world is reflected.